Motivação e Jogos digitais para o Processo de Ensino- Aprendizagem: um estudo sobre suas relações - Nakazoni, Irmgard A. H. C.; Klock, Ana Carolina T.; Gasparini, Isabela; Hounsell, Marcelo da S. (Anais do Workshop sobre Aspectos da Interação Humano-Computador na Web Social (WAIHCWS), 2017)
Motivation is considered as an indispensable factor for carrying out any activity, and particularly learning. Also, it is believed that one way to encourage learning is the use of Digital Games, especially Serious Games as mediating tools of the teaching-learning process. Therefore, we carried out a literature search to identify different motivational theories described in the literature and their application to Digital Games. This paper aims to highlight this relationship towards improving the teaching-learning process.